Modern approaches to emotional development in Russian pedagogy - Irina PAIUL (Acta et Commentationes, Sciences of Education, 2022)
The article presents different views of authors in the scientific community of Russia regarding the complex problem of the emotional development of the human personality. Modern theoretical approaches to emotional development in Russian pedagogical literature, outlined in the content of the article, stimulate the priority directions of the evolution of the pedagogy of emotional culture.